2017
DOI: 10.1108/hff-10-2015-0448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of uniform magnetic field on the natural convection of Cu–water nanofluid in a triangular cavity

Abstract: Purpose The purpose of this paper is to perform a numerical study for heat transfer through natural convection in the presence of a constant magnetic field in an incompressible steady nanofluid flow inside an isosceles triangular cavity. Design/methodology/approach For this flow problem, the left wall of the cavity subjected to uniform/nonuniform heat was considered, while right and bottom walls of the cavity were kept cold. The obtained equations were solved by using the Galerkin weighted residual technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…These will appear soon. Moreover, the considered problem can be extended for convection through square enclosure enclosing (cavity) flow [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…These will appear soon. Moreover, the considered problem can be extended for convection through square enclosure enclosing (cavity) flow [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the average Nu number increases by increasing the nanofluid concentration, depend on both Ha and Ra. Javed et al (2017) numerically investigated the Cu/water nanofluid flow and heat transfer in a triangular cavity in presence of magnetic field. They found that as the Hartmann number increases, the average Nusselt number decreases to a certain value and afterward it becomes constant.…”
Section: Hff 311mentioning
confidence: 99%
“…After using eqs. (10) and (14), the skin friction coefficient and local Nusselt number takes the form:…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Molla et al [13] investigated natural convection flow along a vertical complex wavy surface with uniform heat flux by assuming thermal conductivity of the fluid as constant. Javed et al [14] presented MHD effects of Cu-water nanofluid in a triangular cavity. Mustafa et al [15] discussed MHD mixed convection stagnation point flow of a nanofluid over a vertical plate under the influence of viscous dissipation.…”
Section: Introductionmentioning
confidence: 99%